(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The general budget is described as the main driver for drawing up the economic policy in the country, and the optimal exploitation of the revenues obtained by the state is the best way to achieve economic balance. The achievement of economic balance for any country is closely linked to the type of resources that the government relies on to achieve economic growth, to achieve stability and prosperity for its people. Most of the Middle Eastern (developing) countries, including Iraq, depend on their economy on natural resources, which are known as (what nature provides of things that humans use in their economic activity to satisfy their needs, which were formed as a result of chemical reactions in which humans had no role in forming them, such as oil, gas and coal.